Anti-inflammatory effects of Radix Gentianae Macrophyllae (Qinjiao), Rhizoma Coptidis (Huanglian) and Citri Unshiu Pericarpium (Wenzhou migan) in animal models - Cho Yong-Baik; Han Chang-Kyun; Yoo Hunseung; Kim Ji-Hong; Jeon Hyo; Jung Kiwon; Park Eun; Rhee Hae; Kim Kyoung; Ryu Chun; Yang Hyung; Yoo Myung (BMC, 2008)
Abstract Background KHU14, an ethanolic extract of Radix Gentianae Macrophyllae (Qinjiao), Rhizoma Coptidis (Huanglian) and Citri Unshiu Pericarpium (Wenzhou migan) was tested for its anti-inflammatory effects. Methods Three out of 20 herbs were found to have anti-inflammatory effects. The formulation of these herbs, i.e. KHU14 was tested for croton oil-induced ear edema, carrageenan-induced paw edema, acetic acid-induced capillary permeability, cotton pellet and delayed type hypersensitivity. Results KHU14 exhibited anti-inflammatory effects in animal models of acute and chronic inflammation. The anti-inflammatory activity of KHU14 observed was comparable to that of celecoxib. KHU14 inhibited the production of NO and PGE2 in LPS/IFN-gamma-stimulated peritoneal macrophages, and reduced edema and the amount of infiltrated cells in animal models. Conclusion KHU14 exhibited anti-inflammatory effects as demonstrated in typical immunological tests for anti-inflammation in vitro and in vivo.